Intimate partner violence, associated factors, and psycho-social support networks among pregnant women attending selected health facilities in Isingiro District, Ankole Sub-region, Uganda. A cross-sectional study - Tukamushaba , Edidah; Tweheyo, Anne Otwiine; Katushabe, Eve (Student's Journal of Health Research Africa, 2025)
Background Intimate partner violence (IPV) during pregnancy is a major public health concern with serious consequences for maternal and child health. This study assessed the prevalence, associated factors, and psychosocial support systems for pregnant women experiencing IPV in Isingiro District, Uganda. Methods A mixed-methods cross-sectional design was employed at Rwekubo and Kabuyanda Health Centre IVs, involving 371 participants selected through proportionate stratified sampling. Quantitative data were collected using researcher-administered questionnaires and analyzed with STATA 18, while qualitative data from in-depth interviews with IPV survivors were thematically analyzed using NVivo 15. Results The study enrolled pregnant women aged 20-46 and above, and a high IPV prevalence of 36.5%, higher at Rwekubo (39.2%) than Kabuyanda (32.6%) was found. Predictors included partner substance use (OR = 0.05, p < 0.001), unemployment (OR = 5.07, p = 0.001), and low income, while women earning above UGX 100,000 were less likely to experience IPV. Primary education increased IPV risk (OR = 2.80, p = 0.025). Cultural norms (OR = 27.49, p < 0.001) and limited service awareness (OR = 2.99, p = 0.020) were also significant. Though 56.6% of women reported access to legal protection, it was not statistically protective (OR = 0.72, p = 0.240). Qualitative findings highlighted normalization of marital sexual abuse, stigma, and weak enforcement of services, though peer networks provided emotional support. Conclusion This study provides critical insights into the high prevalence. It demonstrates that IPV in these settings is shaped by a combination of socioeconomic vulnerabilities, partner-related risk factors, especially substance abuse, and entrenched patriarchal norms that normalize violence, particularly sexual and emotional abuse within marriage. Recommendation The study recommends routine IPV screening during ANC, awareness creation, and survivor-centered interventions tailored to rural sociocultural contexts.